Efficiency of Local Exhaust Ventilation System during Stainless Steel Grinding - Dado, Miroslav; Schwarz, Marian; Ockajova, Alena; Hnilica, Richard; Borosova, Daniela (Manufacturing Technology Journal, 2016)
In order to ensure acceptable level of risk associated with exposure to airborne dust they should have been mainly technical and organisation measures at workplaces with enhanced occurance of dust. Local exhaust ventilation (LEV) belongs to principal engineering control for prevention of airborne spreading. The aim of the study was to assess the efficiency of LEV system used at mechanical workshop for controlling respirable fraction of dust during stainless steel grinding activities. Dust control effectiveness was assessed by determining personal exposure levels with and without the use of LEV system. Personal dust samples were collected using a photometer-type dust monitor. On the basis of results it can be concluded that LEV system significantly improved quality of workplace atmosphere at given workplace.
Keywords: Stainless Steel; Grinding Dust; Local Exhaust Ventilation; Photometer